2021
DOI: 10.1161/hypertensionaha.120.16029
|View full text |Cite|
|
Sign up to set email alerts
|

Arterial Remodeling of the Intracranial Arteries in Patients With Hypertension and Controls

Abstract: The intracranial arteries play a major role in cerebrovascular disease, but arterial remodeling due to hypertension has not been well described in humans. We aimed to quantify this remodeling for: the basilar artery, the vertebral, internal carotid, middle/anterior (inferior)/posterior cerebral, posterior communicating, and superior cerebellar arteries of the circle of Willis. Ex vivo circle of Willis specimens, selected from individuals with (n=24) and without (n=25) a history of hypertension, were imaged at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We focussed on the arteries because morphological and mechanical changes of the resistance arteries are often considered a hallmark of hypertension 16 . Multiple animal studies demonstrated that hypertension is associated with remodelling of the cerebral resistance arteries 17 19 , which was also shown in human studies more recently 20 , 21 . Generally, hypertension leads to an increased wall-to-lumen ratio, which can be seen as an adaptation to reduce wall stress.…”
Section: Discussionmentioning
confidence: 58%
“…We focussed on the arteries because morphological and mechanical changes of the resistance arteries are often considered a hallmark of hypertension 16 . Multiple animal studies demonstrated that hypertension is associated with remodelling of the cerebral resistance arteries 17 19 , which was also shown in human studies more recently 20 , 21 . Generally, hypertension leads to an increased wall-to-lumen ratio, which can be seen as an adaptation to reduce wall stress.…”
Section: Discussionmentioning
confidence: 58%
“… 24 , 25 These cardiometabolic risk factors could remodel structure of cerebral blood vessels, thus limiting blood flow, facilitating arteriosclerosis, and reducing oxygen and glucose to the brain. 26 , 27 Therefore, it is biologically plausible that favorable biological CVH profiles are associated with vascular brain health. We did not find any association of CVH profiles with annual PVS changes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers evidenced increased stiffness and histological changes in the inner wall of the internal carotid artery in patients with hypertension. [ 32 ] So, there could be a link between hypertension, arterial calcification, and CVA. Mak et al [ 33 ] identified a high degree of calcification associated with intracranial atherosclerosis and CVA.…”
Section: Discussionmentioning
confidence: 99%